Given the system of equations:
x = 8y + 17 → (1)
x = 5y + 6 →(2)
by substitution by x from the first equation in the second equation
![8y+17=5y+6](https://img.qammunity.org/2023/formulas/mathematics/high-school/tdqm6jsjm5umj84fmnczfm1bn95ni5j1jx.png)
Solve the equation for y
Combine the like terms
![\begin{gathered} 8y-5y=6-17 \\ 3y=-11 \\ \\ y=-(11)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/p2j9bf0os6bmyd7bhpl9kacd4vcp9mvqfu.png)
Substitute with y in the first equation to find x
![\begin{gathered} x=8\cdot-(11)/(3)+17 \\ \\ x=-(88)/(3)+17=-12(1)/(3)=-(37)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/s6r6fxoemb66nmx7etj6sb3jo3su9lfqn4.png)
So, the solution of the system as order pair :
![\begin{gathered} (x,y)=(-(37)/(3),-(11)/(3)) \\ \\ (x,y)=(-12(1)/(3),-3(2)/(3)) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/ii0ixbhzwet0twthsu0ar9h2jc0pxlzxc8.png)